THE MANIFESTATIONS OF BODY BRAZILIAN CULTURE: POSSIBILITIES OF FORMATION OF A LATIN AMERICAN PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
This text aims to relate the events of Body Culture, and the Brazilian social thought of Gilberto Freyre and Roberto Da Matta, through the prism of Brazilian culture, especially in football. Highlight the peculiar ways of designing such events in the formation of a typical Brazilian Physical Education, understanding feelings, creativity, play, and embodiment, as part of daily school.
Keywords: Body Culture; Social Thought; Physical Education